Fluorescence resonance energy transfer enhanced photothermal and photodynamic antibacterial therapy post a single injection. (21st June 2021) - Xue, Lei; Shen, Qing; Zhang, Tian; Fan, Yibin; Xu, Xiaogang; Shao, Jinjun; Yang, Dongliang; Zhao, Wenli; Dong, Xiaochen; Mou, Xiaozhou
Abstract : The constructed near-infrared photothermal nanoparticles (NDIA@PEG-Ce6/B NPs) can enhance the photothermal performance through the FRET effect and can achieve excellent photothermal and photodynamic antibacterial treatment post a single injection. Abstract : Refractory MRSA infections seriously threaten human health, which compromises antibiotic efficacy. Although phototherapy has exhibited great feasibility in the fight against drug-resistant pathogens, a single-modal therapeutic agent without targeted performance has resulted in low drug utilization and obvious side effects. Herein, near-infrared (NIR) light-triggered theranostic nanoparticles (NDIA@PEG-Ce6/B NPs) were prepared by employing naphthalene diimide derivative NDIA as a photothermal agent, PEGylated chlorin e6 (PEG-Ce6) as a photosensitizer and PEGylated phenylboronic acid (PEG-B) as a bacteria-targeting agent. Upon laser irradiation, the singlet oxygen produced by Ce6 can efficiently kill bacteria through photodynamic therapy. Moreover, the fluorescence emission of Ce6 can be absorbed by the photothermal agent NDIA with a fluorescence resonance energy transfer (FRET) efficiency of 78% to reinforce the photothermal effect of NDIA, and the photothermal conversion efficiency of NDIA@PEG-Ce6/B NPs was up to 49.7%. In vitro and in vivo antibacterial experiments indicated that NDIA@PEG-Ce6/B NPs could targeted assembly and effectively destroy multidrug-resistant bacteria through synergistic photothermal and photodynamic therapy with 99.999% antibacterial efficacy under NIR light illumination. The study provides a nanosystem for the antibacterial treatment of synergistic photodynamic and photothermal therapy for subcutaneous abscesses, as well as a novel FRET strategy for further design of light-triggered antibacterial nanoplatforms.